Winners and losers in the platform revolution - J. Christopher Westland (PLoS ONE, 2026)
This study investigates the success and failure of open platform strategies in enhancing firm profitability and value, extending prior research by Parker and Van Alstyne (2018) and Parker et al. (2017). Utilizing an event study methodology, the research examines 52 open platform initiatives across various firms to assess their impact on firm value. The findings highlight a mixed outcome for open platform initiatives, where some events led to significant value creation, while others resulted in value destruction or no impact at all. Successful events often fostered an ecosystem of developers, accelerated innovation, and leveraged strategic advantages, while failures were attributed to strategic misalignment, perceived desperation, and inadequate open-source management. The study concludes that the value derived from open-sourcing depends heavily on aligning initiatives with core business strategies, offering clear value propositions, and engaging robust community management. These insights provide a nuanced understanding of how firms can effectively manage open platform strategies to balance innovation, control, and profitability.